Lower Atmosphere Meteorology - Pérez, Isidro A.; García, M. Ángeles (MDPI - Multidisciplinary Digital Publishing Institute, 2022)
The Atmosphere Special Issue "Lower Atmosphere Meteorology" deals with the meteorological processes that occur in the layer of the atmosphere close to the surface. The interaction between the biosphere and the atmosphere is made through the lower layer and can greatly influence living beings and materials. The analysis of the meteorological parameters provides a better understanding of processes within the lower atmosphere and involved in air pollution, climate, and weather. The mixed layer height, the wind speed, and the air parcel trajectory have a relevant interest due to their marked impact on population and energy production. The research also comprises aerosols, clouds, and precipitation, analysing their spatiotemporal variations. This issue addresses features of gases in the atmosphere and anthropogenic greenhouse emission estimates, which are also conditioned by the lower atmosphere meteorology.